Staggering disease in cats in Sweden : development of molecular methods for detection and genetic characterization of Borna disease virus strains - Schenck, Jessica (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2008)
The aim of this project was to get clearer knowledge about the spread of Borna disease virus (BDV) by comparing sequences from BDV infected cats from different regions in Sweden. BDV is associated with staggering disease (SD), a feline neurological disorder that causes non-suppurative meningoencephalomyelitis. However, cats showing signs for SD are not always confirmed to be BDV infected. In order to get a broader picture of the possible etiological cause/s of SD, molecular screening of viruses using random amplification and sequencing was performed. This study includes eight cats, whereas four were previously positive for BDV in nested RT-PCR and real-time RT-PCR analysis and four cats, only histopathology examined, where three showed signs for SD. Molecular epidemiology approach with RT-PCR and nested RT-PCR for previously positive cats gave PCR products at incorrect as well as correct sizes. However, sequencing showed only feline origin. Since real-time RT-PCR also was negative, one hypothesis is that the RNA had degraded or disappeared through the RNA extraction process. Nested PCR was also performed for the four new cats. Also here the sequencing showed only presence of feline origin. However, for these cats, real-time RT-PCR was positive for the pooled PCR product. Molecular screening of viruses for these four cats showed as before only sequences of feline origin. This project has identified some of the problems of studying RNA viruses present in small amounts in brain tissue. There is always a risk that the RNA is lost during the RNA extraction process. Therefore, further studies are needed to provide more information about the BDV molecular epidemiology in Sweden.